2020
DOI: 10.1016/j.wnsx.2019.100066
|View full text |Cite
|
Sign up to set email alerts
|

Conservative and Surgical Management of Spinal Cord Cavernous Malformations

Abstract: ObjectivesWe present a case series of spinal cord cavernous malformations (SCCMs) to describe clinical presentation and outcomes of both surgical and conservative management.MethodsThe clinical courses of patients diagnosed with SCCMs at our institution were retrospectively reviewed. Neurologic symptoms were evaluated using the Modified McCormick Scale.ResultsA total of 18 patients were identified. Five patients (27.8%) presented with acute onset bleeding, 4 of whom underwent immediate surgical resection. Thir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 28 publications
1
5
1
Order By: Relevance
“…A considerable number of studies investigated possible risk factors leading to first and/or second bleeding [2, 4, 5, 7, 16], but to date no other study has assessed the influence of these risk factors for a third bleeding. Previous studies have assessed an annual risk of haemorrhage of CCM and SCM up to 5% and 10%, respectively [4, 5, 9, 24, 27–30]. Our study revealed an annual rate of 21% for our entire cohort as well as 19% for patients with an SCM, which highlights the rather aggressive course of the disease after a second event.…”
Section: Discussionsupporting
confidence: 54%
“…A considerable number of studies investigated possible risk factors leading to first and/or second bleeding [2, 4, 5, 7, 16], but to date no other study has assessed the influence of these risk factors for a third bleeding. Previous studies have assessed an annual risk of haemorrhage of CCM and SCM up to 5% and 10%, respectively [4, 5, 9, 24, 27–30]. Our study revealed an annual rate of 21% for our entire cohort as well as 19% for patients with an SCM, which highlights the rather aggressive course of the disease after a second event.…”
Section: Discussionsupporting
confidence: 54%
“…According to previous literature, the median duration of primary symptoms to referral was 6.5 months ( 24 ), the mean duration from primary symptoms to subsequent hemorrhage or deteriorative symptoms was 1.42 years and the mean duration from primary symptoms to surgery was 2.1 years ( 25 ). It means those patients with deteriorative symptoms may not be treated by microsurgery timely at most neurosurgical centers.…”
Section: Discussionmentioning
confidence: 95%
“…Even though recently published studies [ 2 , 7 , 28 , 31 ] suggest low surgical risk for resection of SCCM, the variability between single-center studies is high: Deutsch et al (2010) reported in 5 out of 5 patients new dorsal column dysfunction after median myelotomy and cavernoma resection and worsening of McCormick score by one point in 4 out of 5 patients immediately after surgery [ 6 ]. Park et al (2009) report no improvement of sensory symptoms after surgery in their cohort of 14 patients.…”
Section: Discussionmentioning
confidence: 99%
“…As such, the decision for termination of SCCM surgery due to IONM changes anticipating permanent neurological deficit needs a solid ground demanding critical and separate (from other IMSCT entity) analysis. Although several studies have now reported the clinical outcome of surgically treated patients with SCCM [ 1 , 3 , 28 , 38 ], we here report about one of the rare corresponding case series describing microsurgical SCCM resection with stringent utilization of multimodal IONM including both SSEP and MEP—as generally recommended in IMSCT surgeries [ 35 , 39 , 41 ]. Only the study of Li et al (2019) is also reporting about patients who underwent surgery for SCCM with MEP monitoring being available in 52 cases and SSEP monitoring in 32 cases [ 21 ].…”
Section: Discussionmentioning
confidence: 99%